Indonesian Students’ Readiness for the Workforce from the Perspective of the Merdeka Belajar Kampus Merdeka (MBKM) Curriculum - Wargo; Arjmand, Reza; Rahmah, Lina Uliatur (Zabags International Journal of Education, 2025)
The transformation of higher education in the era of the Industrial Revolution 4.0 and Society 5.0 demands graduates who are not only theoretically proficient but also practically competent, adaptable, and ready to face an unpredictable job market. In response to this challenge, the Indonesian Ministry of Education, Culture, Research, and Technology launched the Merdeka Belajar Kampus Merdeka (MBKM) program, aiming to bridge the gap between academic learning and professional demands. This study investigates the extent to which Indonesian undergraduate students are prepared to enter the workforce through their participation in MBKM activities. Employing a qualitative phenomenological approach, the research draws on primary data collected through observations, interviews, and document analysis involving students, academic supervisors, and industry partners at Institut Islam Al-Mujaddid Sabak. The findings reveal that while MBKM fosters discipline, communication, teamwork, and exposure to real-world work environments, students' overall readiness varies depending on internal motivation, emotional maturity, and the quality of institutional support. This article contributes to the discourse on educational reform by offering a multidimensional framework of student readiness, rooted in experiential learning theory, and highlights the need for more inclusive and structured MBKM implementation across higher education institutions in Indonesia.